2015
DOI: 10.1038/srep10903
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Chaperones and Coenzyme Q10 Treatment Improves Mutant β-Glucocerebrosidase Activity and Mitochondrial Function in Neuronopathic Forms of Gaucher Disease

Abstract: Gaucher disease (GD) is caused by mutations in the GBA1 gene, which encodes lysosomal β-glucocerebrosidase. Homozygosity for the L444P mutation in GBA1 is associated with high risk of neurological manifestations which are not improved by enzyme replacement therapy. Alternatively, pharmacological chaperones (PCs) capable of restoring the correct folding and trafficking of the mutant enzyme represent promising alternative therapies.Here, we report on how the L444P mutation affects mitochondrial function in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 50 publications
6
93
0
Order By: Relevance
“…The defects in both autophagy-lysosomal degradation and mitochondrial priming may compromise the autophagic removal of damaged mitochondria, leading to an accumulation of dysfunctional mitochondria and thus mitochondrial oxidative stress. While our data support recent studies in which homozygous GBA mutations alter lysosomal and mitochondrial function via a loss-of-function mechanisms [10,11,38,39], the specific effects of mutant GBA on mitochondrial priming and autophagy induction indicate a gain-of-toxic-function of the mutant protein. This effect may be attributed to the ER retention of mutant GBA protein, resulting in an unfolded protein response [67,68].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The defects in both autophagy-lysosomal degradation and mitochondrial priming may compromise the autophagic removal of damaged mitochondria, leading to an accumulation of dysfunctional mitochondria and thus mitochondrial oxidative stress. While our data support recent studies in which homozygous GBA mutations alter lysosomal and mitochondrial function via a loss-of-function mechanisms [10,11,38,39], the specific effects of mutant GBA on mitochondrial priming and autophagy induction indicate a gain-of-toxic-function of the mutant protein. This effect may be attributed to the ER retention of mutant GBA protein, resulting in an unfolded protein response [67,68].…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies reported both mitochondrial dysfunction and autophagy defects in gba gene knockout GD mouse models and cell cultures [10,11,38,39], suggesting a loss-of-function mechanism of GBA mutations in mitochondrial dysfunction that is associated with GD. It remains unclear, however, whether and how PD-associated heterozygous GBA mutations contribute to mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Other organelles, such as mitochondria and endoplasmic reticulum, and other types of cells, such as type 1 and 2 pneumocyte, appeared normal (Figs. S4, S5), although defects in mitochondrial function have been reported in GD (Gegg and Schapira, 2016, de la Mata et al, 2015). The tubular-like structure was confirmed as lysosome through immunogold EM staining with the lysosomal receptor Sortilin (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of a mouse model representative of neuronopathic GD suggested that isofagomine treatment might restore altered expression levels of miRNA and associated mRNA in processes such as inflammation, axonal guidance pathways, and mitochondrial dysfuntion which are all implicated in PD (108). In another study, patient fibroblasts homozygous for L444P treated with the sp 2 -iminosugars based inhibitory chaperone NAdBT-AIJ revealed amelioration of mitochondrial dysfunction (109). …”
Section: Expert Review and Five-year Viewmentioning
confidence: 95%